Sensory quality of cookies made from chickpea flour (Phaseolus vulgaris L.) and mocaf as non-gluten snacks - Yuniartini, Ni Luh Putu Sherly; Nugrahani, Rizki (Jurnal Agrotek Ummat, 2024)
Cookies are high-fat snacks made from soft dough that have a relatively crunchy texture and a solid cut shape. In an effort to reduce the use of unhealthy wheat flour, cookies can be made from other flours such as chickpea flour and mocaf flour (from cassava). The purpose of this study was to determine the sensory characteristics of cookies from the formulation of two different types of flour (chickpea and mocaf). This study used a completely randomised design (CRD), with 6 treatments, namely: K0 = 0% chickpea flour: Mocaf 100%, K1 = Chickpea Flour 15%: Mocaf 85%, K2 = Chickpea Flour 30%: Mocaf 70%, K3 = Chickpea Flour 45%: Mocaf 55%, K4 = Chickpea Flour 60%: Mocaf 40% and K5 = Chickpea Flour 75%: Mocaf 15%. The results were analysed using analysis of variance (ANOVA) using Microsoft Excel and IBM SPSS Statistics 25.0 applications. If different data was obtained, it was further analysed using BNJ (Differential Real Honest) at the 5% significance level. Based on the results of data analysis, it is known that mixing chickpea flour and mocaf as raw material for cookies has a significant effect on all organoleptic parameters, both Skoring and hedonic methods. Where, the more the addition of chickpea flour and the less mocaf flour, all organoleptic parameters show a tendency of lower values. In conclusion, treatment K0 is the most preferred formulation by the panelists with the Skoring criteria of very yellow colour, very tasteless chickpea flavour and very non-crispy texture. The hedonic criteria for colour and flavour were highly preferred, while texture was preferred.